2017
DOI: 10.1177/1062860617745986
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Benefits to the Use of Patient-Reported Outcome Measures in Routine Clinical Care: A Qualitative Study

Abstract: Patient-reported outcomes (PROs) provide information on how health care affects patient health and well-being and represent a patient-centered approach. Despite this potential, PROs are not widely used in clinical settings. Semi-structured focus groups were conducted with 3 stakeholder groups (patients, providers, and health care administrators) to determine the top 5 perceived barriers and benefits of PRO implementation. The Delphi technique was employed to obtain consensus and rank order responses. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 15 publications
5
79
0
Order By: Relevance
“…Participants believed clinician interest would be a key factor for successful implementation of ePROMs while a lack of awareness among patients and clinicians, time constraints, patients' literacy levels and access to internet/electronic devices were identified as potential barriers to the use of PROMs. These findings are in keeping with the findings presented in a number of previous studies [46,60].…”
Section: Discussionsupporting
confidence: 93%
“…Participants believed clinician interest would be a key factor for successful implementation of ePROMs while a lack of awareness among patients and clinicians, time constraints, patients' literacy levels and access to internet/electronic devices were identified as potential barriers to the use of PROMs. These findings are in keeping with the findings presented in a number of previous studies [46,60].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the findings of Philpot et al (33), the participants suggested omitting redundant questions and adding, for example, photos of the water faucet in question to help their understanding. Examples of questions that did not make sense for the participants in the assessment of functional status (HAQ, MDHAQ), the repetitive character of response options, and the need for questions that have relevance for the patients, are in accordance with the qualitative interview study of Ebbevi et al (34) about how individuals with RA experience the use of HAQ in routine care.…”
Section: Discussionsupporting
confidence: 83%
“…Barriers to implementing PROMs include clinicians believing they do not have the capacity to use them [ 14 , 15 ], clinicians perceiving their practice is being judged on changes in PROMs scores [ 16 ], organisations not having the resources to utilise PROMs, such as no administrative support [ 17 ] and organisations not incorporating PROMs into existing workflows [ 18 ]. There are also factors which facilitate implementation.…”
Section: Introductionmentioning
confidence: 99%